Analysis of Derivate Compound Between Sodium Alendronat with Chloride by High Performance Liquid Chromatography - Yahdiana Harahap; Hayun .; Meriska Sukandar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Sodium alendronate is one of biphosphonate group drugs for the treatment of osteoporosis,. The aim of this research was to obtain the optimum condition for forming derivative of sodium alendronate with dansyl chloride. By adding 270 μL dansyl chloride to 0.1 M sodium carbonate buffer at pH 10.0 mixing with thermomixer at 50.oC for 50 minutes, resulted in a stable derivative within 30 minutes. The compound was analysed by high performance liquid chromatography method using C18 column acetonitrilemethanol-buffer (25 mM KH2PO4 and 25 mM citric acid) (20:15:65;v/v) as mobile phase at a flow rate of 1.0 mL/minute; (detected at wavelength of excitation 320 nm and emission 495 nm). The retention time of the derivative was 19.758 minutes, the calibration’s curve was linear at concentration range of 0.2-1 μg/mL with coefficient of correlation (r) 0.9995 and limit of quantitation 0.114 μg/mL.Key word : HPLC, sodium alendronat, dansyl chloride, fluorescence